Back Trajectories for "Atmospheric Dust Deposition Varies by Season and Elevation in the Colorado Front Range, USA" - Annie Putman; Ruth C Heindel; Sheila F Murphy; Deborah A Repert; Eve-Lyn S Hinckley (PANGAEA, 2020)
Back trajectory runs to accompany analysis of dust at sites near Boulder, CO, USA using the Stochastic Time-Inverted Lagrangian Trajectory model (STILT) run with High Resolution Rapid Refresh reanalysis data. This analysis was performed on the University of Utah extquotesingles High Performance Computer extquotesinglelonepeak extquotesingle. This modeling data may be used with scripts available at https://github.com/putmanannie/FrontRange-Dust; to produce the figures presented in the manuscript and supplemental information.